Integration of the Republic of Turkey To The European Monetary Union - Balcisoy, Kemal Cem (2006)
Turkey as a developing country would like to be part of the European Monetary Union. This study is mainly focused on the economical and social aspects of EMU and Turkey and compare the current variables. Also aanalyses the economical and social similarities in terms of Optimum Currency Area and Monetary Integration aspects.